Modern Professions and the Effectiveness of Digital Economic Systems in Increasing Population Incomes - Xayriddinov Sh. B; Kudratov Shahzod Sarvar o’g’li; Fayziyev Muhammadali Turdiali o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the context of rapid transformations in the global digital market, the significance of utilizing digital technologies by every nation is increasing exponentially. According to DataReportal’s reports on global digital environment trends, compared to 2022, the number of mobile device users increased by 3.2%, internet users by 1.9%, and social media users by 3%. Moreover, it was highlighted that 68% of the world’s population actively engage in communication through digital platforms.